When continuous positive airway pressure (CPAP) fails - Virk, Jagdeep S.; Kotecha, Bhik (Journal of Thoracic Disease, 2016)
Obstructive sleep apnoea (OSA) is increasingly prevalent, particularly in the context of the obesity epidemic, and is associated with a significant social, health and economic impact. The gold standard of treatment for moderate to severe OSA is continuous positive airway pressure (CPAP). However compliance rates can be low. Methodology to improve patient tolerance to CPAP alongside with alternative, non-surgical and surgical, management strategies are discussed. All patients that fail CPAP therapy would benefit from formal upper airway evaluation by the otolaryngologist to identify any obvious causes and consider site-specific surgical therapies. Patient selection is integral to ensuring successful outcomes. A multidisciplinary team is needed to manage these patients.